(untitled) (Swiss Medical Weekly, 2011)
PURPOSE: The two major causative factors for mandibular fractures, as stated in the literature, are either interpersonal violence or motor vehicle accidents. The purpose of this study was to describe epidemiological trends of mandibular fractures in Switzerland. A special emphasis was directed towards the potential impact of socio-economic standards on the mechanism and pattern of mandible fractures. PATIENTS AND METHODS: A database of patients aged over 16 years who had been diagnosed with a mandibular fracture between January 2000 and December 2007 at the University Hospital of Bern, Switzerland’s largest Cranio-Maxillofacial-Surgery Centre, was retrospectively reviewed. Patients’ data including gender, age, mechanism of accident, fracture site and associated injuries were analysed and compared with previously published data. RESULTS: There were a total of 420 patients with 707 mandibular fractures. The two most common causes of injury were road traffic accidents (28%) and various types of sports injuries (21%). A total of 13% of the patients were under the influence of alcohol or drugs at admission. Fractures were predominantly situated in the condyle/subcondyle (43%) and in the symphysis/parasymphysis region (35%). Occurrences of fractures in the angle and in the body were low, at 12% and 7% respectively. CONCLUSION: In contrast to other highly developed countries, sports- and leisure-related accidents outnumbered motor vehicle accidents and altercations. The data presented here supports the assumption of a correlation of trauma cause and fracture pattern.